Epidemiological dynamics and early warning of norovirus and rotavirus A in Yantai City in 2023-2024 based on wastewater surveillance - Yan, Shicui; Xu, Guofeng; Ding, Xuebin; Zhao, Lili; Gao, Qiao; Li, Cong; Wang, Hongtao; Tao, Zexin; Sun, Zhenlu (Frontiers in Microbiology, 2026)
ObjectiveThe aim is to address the limitations of clinical surveillance—specifically, its high cost and underreporting of asymptomatic infections and untreated individuals—by implementing municipal wastewater surveillance. This study characterizes the epidemiological dynamics of Norovirus (NoV) and Rotavirus A (RVA) in Yantai City and evaluates the effectiveness of Wastewater-Based Epidemiology (WBE) for early outbreak warning.MethodsFrom 2023 to 2024, weekly wastewater samples (1–2 samples per site) were collected from 10 municipal wastewater treatment plants (WWTPs) across five urban districts and three counties in Yantai City. Following concentration via polyethylene glycol (PEG) precipitation, viral nucleic acids of NoV GI/GII and RVA were examined using multiplex reverse transcription quantitative PCR (RT-qPCR), with quantification based on standard curves. Cross-correlation analysis was applied to assess time-lag relationships between viral concentrations in wastewater and clinical case peaks, and to evaluate the statistical significance (α = 0.05) of the early warning time window.ResultsWastewater surveillance (no. samples: 1,391) identified NoV GII as the dominant virus with an overall detection rate of 85.84%. However, from 2023 to 2024, its annual detection rate declined significantly from 92.27% to 73.81% (P < 0.001). During the same period, NoV GI also declined annually from 83.55% to 69.07% (P < 0.001), whereas RVA detection increased substantially by 145.7% annually, rising from 26.6% to 65.36% (P < 0.001). NoV peaked in winter-spring seasons (GI: 76.61% in winter, 89.20% in spring; GII: 87.13% in winter, 91.31% in spring), whereas RVA peaked in spring (42.72%) and summer (55.79%). Seasonal fluctuation intensity followed this order: RVA (χ2 = 69.07) > NoV GI (χ2 = 49.28) > NoV GII (χ2 = 21.44). Cross-correlation analysis indicated that NoV GII concentration in wastewater peaked 1 month ahead of clinical cases, showing significant positive correlations with both reported cases (r = 0.60, P = 0.002) and clinical positivity rates (r = 0.53, P = 0.009) at a one-month lag. A one-month lag for NoV GI and a two-month lag for RVA relative to clinical cases were observed but were not statistically significant (P > 0.05).ConclusionSystematic wastewater surveillance effectively captured population-level epidemiological dynamics of NoV and RVA. Notably, NoV GII provided a significant one-month early warning signal (P < 0.01), establishing its value as a leading indicator for diarrheal virus prevention and control in Yantai City.